Bulgaria : Teachers - World Bank (Washington, DC, 2014)
Bulgaria implemented sweeping decentralization and efficiency-focused reforms in basic education in 2007 and 2008. The education system adjusted to the negative demographic trends by optimizing the network of schools (closing and merging schools), introducing per-capita based financing and delegating significant financial and decision-making autonomy to school principals. This policy reform package produced a number of benefits for the education sector; it accrued savings of over 100 million BGN and increased wages by 46 percent and reallocation of resources for capital investment (World Bank 2010). Despite the government's impressive achievements in terms of spending efficiency and high enrollment, lingering concerns remain about the quality and equity of the education system. The country has seen a negative trend in student learning outcomes as measured by international assessments. At the request of the Government of Bulgaria, the World Bank has implemented its newly developed tool for assessment and benchmarking of policies and programs affecting teacher's effectiveness Systems Approach for Better Education Results (SABER) teachers. The key findings and policy options outlined in the present report are intended to inform the finalization of the new draft law and the development of the bylaws regulating teachers' policies in Bulgaria. This report presents results of the application of SABER-teachers in Bulgaria. It describes Bulgaria's performance in each of the eight teacher policy goals, alongside comparative information from education systems that have consistently scored high results in international student achievement tests and have participated in SABER-teachers. Additional detailed descriptive information on Bulgaria's and other education systems' teacher policies can be found on the SABER-teachers website.